2012
DOI: 10.1093/bja/aes247
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil during cardiac surgery is associated with chronic thoracic pain 1 yr after sternotomy

Abstract: In this follow-up study in cardiac surgery patients, intraoperative remifentanil was predictive for chronic thoracic pain in a dose-dependent manner. Randomized studies designed to evaluate the influence of intraoperative remifentanil on chronic thoracic pain are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 22 publications
(13 reference statements)
4
80
2
5
Order By: Relevance
“…Only two studies reported on the influence of high doses of intraoperative opioids on the risk of developing PPSP. 36 Better studies are required to draw a strong conclusion on whether acute OIH might participate in the development of PPSP, especially since most of the data are from animal studies and evidence in humans is less compelling, even if publications have been more numerous in recent years.…”
Section: Mechanism Of Ppsp Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies reported on the influence of high doses of intraoperative opioids on the risk of developing PPSP. 36 Better studies are required to draw a strong conclusion on whether acute OIH might participate in the development of PPSP, especially since most of the data are from animal studies and evidence in humans is less compelling, even if publications have been more numerous in recent years.…”
Section: Mechanism Of Ppsp Developmentmentioning
confidence: 99%
“…Seulement deux études rapportent des résultats quant à l'influence de hautes doses d'opioïdes peropératoires sur le risque de développer des DCPC. 36 De meilleures études cliniques sont nécessaires pour tirer une conclusion plus définitive sur le fait que l'OIH précoce pourrait participer au développement des DCPC. Malgré des données provenant d'études animales en ce sens, les données recueillies chez l'homme sont moins convaincantes, et ce, en dépit de publications plus nombreuses ces dernières années.…”
Section: Mécanismes Physiologiques Du Développement Des Dcpcunclassified
“…1 study investigated the role of chronic nonanginal pain before surgery as a contributing factor; 21 5 others prospectively assessed the association between persistent postoperative pain and acute pain intensity in the first postoperative week but reported conflicting results. 13,14,21,22,25 All of the above studies were carried out in a single hospital and included relatively small samples.…”
Section: Methodsmentioning
confidence: 99%
“…13,14,21,22,25 All of the above studies were carried out in a single hospital and included relatively small samples. None of the studies examined the contribution of psychological factors such as levels of anxiety and depression before cardiac surgery, although these factors have been shown to influence acute or persistent postoperative pain in other types of surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation